Three cities in the science fiction cinema:: Dystopias and the consolidation of a flexible accumulation regime - Vielma Cabruja, Jose Ignacio (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
Three turn of century mainstream films which represent the inmediate future city are revised (The Truman Show, Code 46 and The Island). They share to be describable using the concept of dystopia (bad place). The purpose is to identify relations with the con-temporary processes of urbanization and production, as they are described in recent criticism and urban sociology. The emergence and consolidation of a flexible accumulation regime is recognized in the works. The analytical and relational description of the films is made around the strategies of control over the social, production, subject and urban space of dystopian societies. Is verified that there, very relevant part of the dysto-pia’s own conditions coincides empirically with the processes and consequences of a hy-pothetical hegemony of advanced capitalism within the productive and cultural frame-work.